Otherworldly Relations in CAM Practice: Towards an Ethnography of Non-Secular Possibility Work - Utriainen Terhi (FINNISH SOC STUDY RELIGION, 2022)
The globalizing culture of health and wellbeing flourishes both as demand and supply, posing multiple intriguing and critical questions both to the individuals who face distress and suffering and to the surrounding society. In the spirit of vernacular religion, this article enters the discussion of 'de-differentiation' between religion and health, focusing especially on the role of otherworldly relations that may become part of complementary and alternative medicine and care and its healing agency. I propose that engagement with otherworldly relations may be understood in terms of 'possibility work' in complex life situations when conventional healthcare and therapy are apprehended as insufficient for some reason, or alternatively unavailable. I draw on two distinct ethnographic projects to exemplify the argument: care of the dying and contemporary angel spirituality. These two examples demonstrate how intimate otherworldly relations may work as important and powerful, albeit also ambivalent and socially vulnerable, non-secular possibility work in the face of various forms of anxiety, distress, and suffering in contemporary lives.